Pendidikan Adab Dalam Perspektif Pemikiran Imam Nawawi Dalam Kitab At-Tibyan Fi Adabi Hamalatil Quran - Muhammad Jaka Samudra; Zailani Zailani (PT. ALHAFI BERKAH INDONESIA, 2023)
The decline in the problem of adab in the world of education has an impact on the destruction of civilization. Therefore it is very important to educate the etiquette of a teacher and the etiquette of a student of knowledge. Adab education requires guidelines that are in accordance with the Al-Quran, As-Sunnah, and the opinions of the scholars as the essence in providing solutions to every problem. In this regard, in the book At-Tibyan Fi Adabi Hamalatil Quran, Imam Abu Zakaria Yahya bin Syaraf An-Nawawi summarizes adab education. The method of this research is library research (library research), which is a research that utilizes library sources to obtain data using a concept study approach/figure thinking. The results and conclusions of this study are that there are 15 etiquette etiquette for teachers and 20 etiquette education for students.